3D modelling of the impacts of in-stream horizontal-axis Tidal Energy Converters (TECs) on offshore sandbank dynamics. (October 2019) - Chatzirodou, Antonia; Karunarathna, Harshinie; Reeve, Dominic E.
Highlights: The impacts of arrays of Tidal Energy Converters (TECs) on the sea bed morphology are investigated. A 3D hydrodynamic and morphodynamic model is set up to study the impacts of TECs. The Pentland Firth, Inner Sound Channel, UK is used as the test site. It is proved that TECs installation may have significant impacts on mobile sea bed areas. TECs impacts depend on array proximity to sea bed areas, array configuration and energy extraction levels. Abstract: The tidal energy sector is a growing industry in the UK and beyond. Energy developers' interests are progressing towards the deployment of large arrays of tidal energy converters (TECs). Numerous factors will affect decision making related to arrays siting and size. One key factor is the effect that the TEC arrays may have on the natural sediment transport patterns and the sea bottom morphodynamics. The Inner Sound Channel located between the Island of Stroma of Pentland Firth and the Scottish Mainland (UK) has been accredited for a large-scale TEC array installation to be developed in the future. Three morphodynamically active, large sandbanks are located in the Inner Sound channel. This study investigated the impacts of tidal energy extraction from a large array of TECs on the sediment dynamics and morphology of these sandbanks. A large-scale 3D hydrodynamic and morphodynamic Delft3D model was set up to computationally model Pentland Firth, Inner Sound Channel in order to study the impacts of tidal energy extraction from a generic TEC array, on the existing hydrodynamic and morphodynamic regime. A range of hypothetical energy extraction scenarios was modelled. Results reveal that the changes to morphodynamics of these sandbanks as a result of large scale tidal energy extraction far exceeds the morphology change under the natural hydrodynamic regime and that the severity of morphology change depends on the level of energy extraction.